An annotated list and molecular data on larvae of gryporhynchid tapeworms (Cestoda: Cyclophyllidea) from freshwater fishes in Africa - Tavakol, Sareh; Scholz, Toma´sˇ; Uhrova´, Lucie; Brabec, Jan; Prˇikrylova, Iva; Masˇova´, S ˇ a´rka; S ˇ imkova´, Andrea; Halajian, Ali; Luus-Powell, Wilmien J. (Syst Parasitol, 2018)
An annotated list of larvae (metacestodes) of gryporhynchid tapeworms (Cestoda: Cyclophyllidea) from freshwater fishes in Africa is provided with numerous new host and geographical records. Newly collected materials from Burundi, Democratic Republic of the Congo, Kenya, Madagascar, Namibia,Senegal, South Africa, Sudan and Zimbabwe practically double the total number of species reported from African fish so far. We confirm the occurrence of 16 species (five unidentified to the species level and most likely representing new taxa) belonging to the genera Amirthalingamia Bray, 1974 (1 species), Cyclustera Fuhrmann, 1901 (2 species), Dendrouterina Fuhrmann, 1912 (1 species), Neogryporhynchus Baer & Bona, 1960 (1 species), Paradilepis Hsu¨ , 1935 (4 species), Parvitaenia Burt, 1940 (5 species), and Valipora Linton, 1927 (2 species). Additionally,metacestodes of four unidentified species of Paradilepis and Parvitaenia are reported from fish for the first time. Rostellar hooks of all species are illustrated and their measurements are provided together with a host-parasite list. The molecular phylogenetic analysis based on partial LSU rDNA sequences offers the first insight into the internal phylogenetic relationships within the family. Together with the morphological observations, the present study provides a taxonomic baseline for future studies on this largely neglected, but widely distributed and relatively frequent, group of parasites of African fishes, including economically important cichlids like tilapias and cyprinids.
Article published in the Syst Parasitol (2018) vol 95:567–590 https://doi.org/10.1007/s11230-018-9796-y
Keywords: Molecular data; Larvae; Gryporhynchid tapeworms (Cestoda: Cyclophyllidea); Freshwater fishes; Aquatic biodiversity; Fishes-Parasites-Control-Environmental aspects